Assessment of Behavior Factor for Steel Plate Shear Wall with Reinforced Concrete Moment Surrounded Frame - Madjid Gholhaki (Iranian Society of Structrual Engineering (ISSE), 2019)
The steel shear wall is an appropriate resistant system against lateral loads that is been utilized in modern high-rise buildings and upgrading existing buildings because of numerous benefits. This article examined the operation usage of this system in compound reinforced concrete moment frame using suggested connections (additional stirrup). According to this, a steel shear wall three-story reinforced concrete single bay frame (suggested connections) modelled and the plastic behavior and its behavior factor with the reinforced concrete frame, stud connections, and bare reinforced concrete moment frame compared. The result showed that the behavior factor system comparing to bare reinforced concrete frame and reinforced concrete frame contains the steel shear wall with stud connections have increased and about 6.5 (the extent) can be considered.The steel shear wall is an appropriate resistant system against lateral loads that is been utilized in modern high-rise buildings and upgrading existing buildings because of numerous benefits. This article examined the operation usage of this system in compound reinforced concrete moment frame using suggested connections (additional stirrup). According to this, a steel shear wall three-story reinforced concrete single bay frame (suggested connections) modelled and the plastic behavior and its behavior factor with the reinforced concrete frame, stud connections, and bare reinforced concrete moment frame compared. The result showed that the behavior factor system comparing to bare reinforced concrete frame and reinforced concrete frame contains the steel shear wall with stud connections have increased and about 6.5 (the extent) can be considered.